1994
DOI: 10.1148/radiographics.14.2.8190950
|View full text |Cite
|
Sign up to set email alerts
|

Duplex and color Doppler sonography of complications after percutaneous interventional vascular procedures.

Abstract: Duplex and color Doppler sonography have proved to be excellent noninvasive modalities for evaluating complications of percutaneous interventional vascular procedures. Complications including hematoma, pseudoaneurysm, arteriovenous fistula, thrombosis, stenosis,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Nevertheless, the Pathobiological Determinants of Atherosclerosis in Youth (PDAY) study confirmed that atherosclerosis development occurs at an early age (49,50) and it is worthwhile to have ready a noninvasive detection method to track serious cases starting at an early age. MR visualization and quantification of flow patterns may also have value for evaluation and follow-up of vascular interventional procedures, given the present use of Doppler ultrasound in assessing vascular interventional complications (51)(52)(53)(54)(55)(56), and the importance of flow patterns in mediating the anastornotic endothelial response (57).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the Pathobiological Determinants of Atherosclerosis in Youth (PDAY) study confirmed that atherosclerosis development occurs at an early age (49,50) and it is worthwhile to have ready a noninvasive detection method to track serious cases starting at an early age. MR visualization and quantification of flow patterns may also have value for evaluation and follow-up of vascular interventional procedures, given the present use of Doppler ultrasound in assessing vascular interventional complications (51)(52)(53)(54)(55)(56), and the importance of flow patterns in mediating the anastornotic endothelial response (57).…”
Section: Discussionmentioning
confidence: 99%
“…Colour Doppler sonography depicts fistulas by means of high velocity and turbulent flow at the site of the lesion, low-resistance arterial signals as well as highvelocity venous outflow; usually marked colour artefacts due to vibration of surrounding perivascular tissues coexist [104]. Colour Doppler sonography locates the site of the fistula with accuracy; conversely, angiography often cannot help identify the exact position and the size of the track because of the very fast and intense vein opacification.…”
Section: Local Iatrogenic Lesionsmentioning
confidence: 99%
“…Clinically, it presents as a nonpulsatile mass or ecchymosis at the puncture site. Gray-scale sonographic images of a perivascular hematoma show a softtissue mass with varying echogenicity in the inguinal area, adjacent to the femoral artery [ 4 ]. The echogenicity of a hematoma may vary depending on how long it has been hemorrhaging; therefore, it can be mistaken for a cyst or solid mass ( Fig.…”
Section: Hematomasmentioning
confidence: 99%
“…Duplex ultrasound, which consists of gray-scale and color Doppler ultrasound, has proven to be an excellent noninvasive modality that provides not only anatomic but also hemodynamic information [ 4 ]. Although ultrasonography has limited utility for evaluating patients with a poor echo window due to obesity or a large swelling, it should be used to establish a preliminary diagnosis, especially for patients with a palpable mass or an audible bruit.…”
Section: Introductionmentioning
confidence: 99%